Structural Challenges in Constructive Muslim Thought on Gender and Sexuality. - Hidayatullah, Aysha (Muslim World)
Constructive Muslim scholarship engaged in the critique of hierarchies which are based on gender and sexuality faces structural challenges posed by both Muslim community audiences and the academy. These challenges produce limitations but also generate key theological insights within Muslim constructive thought. This critical constructive scholarship must necessarily attend to both the present and future of Muslim communities.